Martin Demant Frederiksen – Ida Harboe Knudsen (eds.): Modern Folk Devils. Contemporary Constructions of Evil - Kubelka, Michal (Lidé města, 2022)
A review of the book by Martin Demant Frederiksen and Ida Harboe Knudsen.